MAKNA SIMBOL KOMUNIKASI DALAM BUSANA TARI JAUK MANIS - Agung Mataram, Gusti Gede; Sugiarica Joni, I Dewa Ayu; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium, 2018)
ABSTRACT Dance costume is a form of non-verbal communication in which there are symbols that have meaning in accordance with the purpose of the dance. This can be seen in one of the dance costumes in Bali, namely Jauk Manis Dance. In Jauk Manis Dance costume, there is a conclusion that there is non-verbal communication with the contents of cultural values ??conveyed through the symbols attached to it. This study aims to determine the meaning of communication contained in Jauk Manis Dance costume. Texts and costume symbols of Jauk Manis Dance were chosen as research objects because the symbols in Jauk Manis Dance costume contained meanings and values ??related to Balinese culture and beliefs. This research uses descriptive qualitative method and uses Roland Barthes Semiotics Theory. The results show that there are meanings and values ??behind the symbols attached to Jauk Manis Dance costume such as: cultural values, religious values ??and artistic values. Cultural value in which costume describes a particular group of people. Religious value in the choice of colors is a symbol of the strength of the Gods in the belief of Hinduism. While the value of art in which there are ornaments and motifs in costume that aims as a decoration to beautify the appearance of costume Keywords: Meaning of Symbols, Semiotics, Dance Costume, Jauk Manis Dance